Elevated factor VIII and mesenteric vein thrombosis - P Murali Krishna; K Sravan Kumar; L R S Girinidh; Allu R Kumar (Journal of Dr. NTR University of Health Sciences, 2018)
Elevated concentrations of factor VIII have recently been associated with de novo development of deep vein thrombosisand its recurrence Occurrence of mesenteric vein thrombosis in patients with elevated factor VIII has been rarely described but not well characterized. We describe in this article a young patient who developed superior mesenteric vein thrombosis and on evaluation was found to have abnormally elevated factor VIII.